Explicating change in pre-service mathematics teachers education using the elements of lesson study - Elipane, Levi Esteban (Animo Repository, 2012)
This study explores how the elements of 'Lesson Study' are being utilized as a powerful intervention in order to facilitate the transition of prospective mathematics teachers from being students in methods courses into undergoing actual teaching practice in schools during the student teaching program. A single case of student teaching program in a Fuzoku school in Japan was highlighted in the hope of elevating certain ruminations on how change was brought about by legitimizing and nurturing the essential features of Lesson Study in pre-service mathematics teacher education. The daily journal completed by a student teacher served as the main source of data that acted as a window to his reflective stances and emotional engagements while he was undergoing his practicum. Also, observations, interviews, and analysis of artefacts, such as the student teacher's notes and lesson plans, facilitated in the crystallization of data. Findings of this study attempt to elucidate how, for a short period of time, significant change in attitudes and development of habits of mind could be possibly forged among student teachers during their practicum.